Imagery Rehearsal Based Art Therapy: Treatment of Post-traumatic Nightmares in Art Therapy - Haeyen, Suzanne; Staal, Merel (Frontiers in Psychology, 2021)
Imagery Rehearsal Therapy (IRT) is effective for trauma-related nightmares and is also a challenge to patients in finding access to their traumatic memories, because these are saved in nonverbal, visual or audiovisual language. Art therapy (AT) is an experiential treatment that addresses images rather than words. This study investigates the possibility of an IRT-AT combination. Systematic literature review and field research was conducted, and the integration of theoretical and practice-based knowledge resulted in a framework for Imagery Rehearsal-based Art Therapy (IR-AT). The added value of AT in IRT appears to be more readily gaining access to traumatic experiences, living through feelings and breaking through avoidance. Exposure and re-scripting take place more indirectly, experientially and sometimes in a playlike manner using art assignments and materials. In the artwork, imagination, play and fantasy offer creative space to stop the vicious circle of nightmares by changing theme, story line, ending, or any part of the dream into a more positive and acceptable one. IR-AT emerges as a promising method for treatment, and could be especially useful for patients who benefit least from verbal exposure techniques. This description of IR-AT offers a base for further research.